IMPLEMENTASI ASPEK HUKUM STANDAR PELAYANAN MINIMUM PADA PASIEN BPJS TINJAUAN FATWA DSN MUI NO. 107/DSN-MUI/X/106 TENTANG PEDOMAN PENYELENGGARAAN RUMAH SAKIT BERDASARKAN PRINSIP SYARIAH STUDI DI RUMAH SAKIT UMUM DAERAH KABUPATEN JOMBANG - Wildani Mahaldyan Syach (Journal of Islamic Business Law, 2018)
This research aims to know the level of patient satisfaction BPJS and implementation SPM as well as tinjauannya according to the fatwa DSN MUI No. 107/DSN-MUI/X/106. This research is a kind of juridical research empirical juridical sociological approach. Data analysis methods in use is descriptive analysis method. Results of the study amounted to 50 respondents .36 people are satisfied with the service provided includes field service dimensions of physical evidence, guarantee and attention. While the 14 people declared not satisfied includes field service responsiveness and reliability. Such things are certainly very influential towards the Ministry because the patient is the main source of the Ministry. About the review according to the fatwa DSN MUI No. 107/DSN-MUI/X/106 that RSUD Kabupaten Jombang has adopted an indirect indicator of the fatwa, namely in the field of services, medicines, food and drink.